Micro-Small-Medium Enterprise (MSMEs) Entrepreneurs’ Financial Literacy and MSMEs Financial Performance (Journal of Business and Management, 2022)
The urgent pressures from the government to MSMEs for the national economic growth, the high gap between financial inclusion and financial literacy because of many people who have limited knowledge and understanding of financial products and services, and the internal problem that are the lacking of risk management, strategic planning, and the ability to detect signs of internal problems and financial health by the entrepreneurs, make the urgency become more critical for the entrepreneurs to understand that financial literacy skill is needed in order to create better performance in economic goals. In accordance with the statement, the purpose of this research is to figure out the financial literacy influences in the MSMEs’ financial performance management. To measure the impact, the researcher uses financial knowledge, financial behavior, and financial attitude as indicators for financial literacy and subsequently uses a quantitative approach with Multiple Linear Regression (MLR) Analysis to analyze the data. The sample included 132 MSMEs entrepreneurs all over Indonesia. The results of the data analysis shows that only MSMEs entrepreneurs’ financial attitude has a positive effect on financial performance management. Meanwhile, financial knowledge has a negative impact on financial performance management and financial behavior has no effect on financial performance management. The findings are useful for MSMEs entrepreneurs to be more aware of their own financial ability that can give impact to the MSMEs development.Keywords: Financial Literacy, Financial Knowledge, Financial Behavior, Financial Attitude, MSME’s Financial Performance Management, Multiple Linear Regression (MLR)